2018
DOI: 10.1177/0892705718808555
|View full text |Cite
|
Sign up to set email alerts
|

γ-Irradiated gelatin and polyvinyl alcohol films as artificial articular cartilage

Abstract: Both gelatin and polyvinyl alcohol polymers have good biocompatibility to be used in biomedical applications. Cell adhesion and growth activity of gelatin have made it unique in artificial cartilage preparation. Two separate solutions of them are prepared by mixing 10% (w/v) of each one in water. These two solutions are then mixed at a temperature range of 70–90°C, and a pH value of 2 is maintained and finally it is cast into films. The dried films are gamma irradiated (using 60Co) at different doses. Fourier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…Literature search demonstrated a various ratio of gelatin to PVA that has been reported in the selected articles. Al-Mamun et al [52] and Ebnalwaled et al [55] reported a 1:1 ratio of gelatin to PVA. In contrast, Basak et al [53] and Chaibi et al [50] used fixed ratios, which are 1:2 and 29:43, respectively.…”
Section: Fabrication Of Gelatin-pva Filmmentioning
confidence: 99%
See 3 more Smart Citations
“…Literature search demonstrated a various ratio of gelatin to PVA that has been reported in the selected articles. Al-Mamun et al [52] and Ebnalwaled et al [55] reported a 1:1 ratio of gelatin to PVA. In contrast, Basak et al [53] and Chaibi et al [50] used fixed ratios, which are 1:2 and 29:43, respectively.…”
Section: Fabrication Of Gelatin-pva Filmmentioning
confidence: 99%
“…As for gelatin, the final concentrations used by Chaibi et al [50] and Ismaiel et al [51] are almost similar, which are 0.05 and 0.048 g/mL, respectively. In contrast, Al-Mamun et al [52] used a higher concentration of 0.11 g/mL. Another study performed by Basak et al [53] described 5% of gelatin, however, Jain et al [54] used three different percentages of gelatin that are 1%, 2% and 3%.…”
Section: Fabrication Of Gelatin-pva Filmmentioning
confidence: 99%
See 2 more Smart Citations
“…W ciągu ostatnich dwóch dekad wzrosło zapotrzebowanie na naturalne materiały bioaktywne, gdyż nie wykazują toksyczności i są bezpieczniejsze w użytkowaniu niż polimery syntetyczne. Dużym zainteresowaniem w naprawie i regeneracji uszkodzonej tkanki cieszą się: chitozan, kolagen, żelatyna, alginian, fibroina, hydroksyapatyt czy kwas hialuronowy [12]. Ze względu na unikalne właściwości i dostępność chitozan był szeroko badany jako potencjalny materiał bioaktywny i stał się obiecującym materiałem w inżynierii tkankowej [10].…”
Section: Potencjał Chitozanu W Zastosowaniach Nowoczesnych Metod Inży...unclassified